A capacitor-based DC circuit breaker for HVDC power grid - Xu, Zhuang; Liang, Jun; Guo, Yanxun; Wang, Yaoqiang (Frontiers in energy research, 2022)
DC circuit breakers (DCCBs) are the critical equipment to isolate faults in high-voltage DC grids. The improvement of interruption performances of capacitor-based DCCBs (C-DCCBs) has been widely researched. However, in previous papers, the adaptive reclosing of C-DCCBs is less considered and requires further research. In this paper, a novel C-DCCB with adaptive reclosing ability is proposed. The interruption and adaptive reclosing processes of the proposed C-DCCB are presented. The fault current is interrupted by charging the internal capacitor to a voltage higher than the system voltage. The fault property identification is key to adaptive reclosing and is achieved using the capacitor discharge characteristic. The parameter designs are analyzed to guarantee successful interruptions, and the identification criteria are proposed to serve the adaptive reclosing. On the one hand, the proposed C-DCCB has good interruption performances; on the other hand, an adaptive reclosing strategy is designed for the proposed C-DCCB to restore the power transmission whereas avoiding a second fault shock, which is the main contribution of this paper. Finally, the interruption and adaptive reclosing performances of the proposed C-DCCB are validated using PSCAD/EMTDC simulations.